A comparison between positive and native anxiety between of women basketball players (×ࢿ3) according to the playing roles - SABAH JASIM, YASAR; Jabar Mahmoud, Sanaria; MOHAMMED MGHAMESS, MUNTADHER (International Journal of Psychosocial Rehabilitation, 2020)
The research includes five chapters: First chapter: Introduction and search are important as they involve knowing the comparison between the worry level among basketball players (×ࢿ3) for women because it is a new game and contains three places in the playground, and the research aims to know the sport worry degree {easy, difficult} for basketball players (×ࢿ3) for women in Iraq who are competitive in Sulamaniy and contain {24} players. Second chapter: Include the theory studies. The researcher indicated to some subjects such as the concept of worry and {kinds, sources} and the concept of worry in the sports field. Third chapter: Involving the methodology of research and field procedures, the researcher used the adjectival research. Fourth chapter: Include deals, analysis, and discussion on the result of research that contains the result of sport measure {easy, difficult} for basketball players. Fifth chapter: Include the inference and recommendation. The researcher gets to some result as follows: Find the effect of worry measurement {easy, difficult} of basketball players by a few rates. And the researcher recommended continuous work on surmounting the difficulties during the training and, especially, the psychological programs such as {fear}.